A novel high capacity turtle shell-based data hiding with location table free. (4th May 2020) - Lin, Jiang-Yi; Chen, Yu; Chang, Chin-Chen; Hu, Yu-Chen
In this paper, we design a novel turtle shell based data hiding scheme. The proposed scheme starts by constructing a novel reference matrix based on the original turtle shell matrix. Without any overhead messages, the secret data can be concealed in the pixel pairs selected from the cover image and would be correctly extracted according to the characteristic of the reference matrix in a 4 × 5 block. Experimental results demonstrate that the proposed scheme can achieve a high embedding capacity of 2 bit per pixel (bpp). The experimental comparison also reveals that the proposed scheme is superior to some existing data hiding schemes subject to the peak signal-to-noise ratio measurement. Meanwhile, it has good performance on resisting the statistical attack of pixel-value differencing (PVD) histogram.